Sonic Hedgehog signaling limits atopic dermatitis via Gli2-driven immune regulation - Papaioannou, Eleftheria (J Clin Invest, 2019)
Hedgehog (Hh) proteins regulate development and tissue homeostasis, but their role in atopic dermatitis (AD) remains unknown. We found that on induction of mouse AD, Sonic Hedgehog (Shh) expression in skin and Hh pathway action in skin T cells were increased. Shh signaling reduced AD pathology and the levels of Shh expression determined disease severity. Hh-mediated transcription in skin T cells in AD-induced mice increased Treg populations and their suppressive function through increased active transforming growth factor–β (TGF-β) in Treg signaling to skin T effector populations to reduce disease progression and pathology. RNA sequencing of skin CD4(+) T cells from AD-induced mice demonstrated that Hh signaling increased expression of immunoregulatory genes and reduced expression of inflammatory and chemokine genes. Addition of recombinant Shh to cultures of naive human CD4(+) T cells in iTreg culture conditions increased FOXP3 expression. Our findings establish an important role for Shh upregulation in preventing AD, by increased Gli-driven, Treg cell–mediated immune suppression, paving the way for a potential new therapeutic strategy.